1993
DOI: 10.1051/jp4:1993916
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of ODS alloys

Abstract: NiCr, NiCrAl and FeCrAl based Oxide Dispersion Strengthened (ODs) high temperature alIoys possess far better oxidation resistance than dispersion free alloys of the same base composition. The presence of yttria dispersions leads to excellent scale adherence and a very selective oxidation of the scale forming element. Most of the observed differences in microstructure and protective properties between oxide scales on ODs and non-ODs alloys can be explained by differences in scale transport mechanisms. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 9 publications
(13 reference statements)
0
20
0
Order By: Relevance
“…1 Therefore, the strengthening imparted by the oxide dispersions is retained up to very high temperatures because only limited coarsening or dissolution of the particles occurs. 2,3 In addition, the presence of the fine dispersions combined with a very coarse-grained microstructure that is stable over long exposure times leads to excellent creep resistance up to higher temperatures than those that can be achieved with conventional wrought or cast alloys. 4,5 The ODS alloys commercially produced at the end of the 20 th century and the beginning of the 21 st century are represented by MA 956 or MA 957 6 , PM 2000 or PM 2010 6 , ODM alloys 7 and 1DK or 1DS 8 with a ferritic matrix by ODS Eurofer steels with a tempered ferriticmartensitic matrix 9 and by austenitic Ni-ODS PM 1000 or Ni-ODS PM 3030.…”
Section: Introductionmentioning
confidence: 99%
“…1 Therefore, the strengthening imparted by the oxide dispersions is retained up to very high temperatures because only limited coarsening or dissolution of the particles occurs. 2,3 In addition, the presence of the fine dispersions combined with a very coarse-grained microstructure that is stable over long exposure times leads to excellent creep resistance up to higher temperatures than those that can be achieved with conventional wrought or cast alloys. 4,5 The ODS alloys commercially produced at the end of the 20 th century and the beginning of the 21 st century are represented by MA 956 or MA 957 6 , PM 2000 or PM 2010 6 , ODM alloys 7 and 1DK or 1DS 8 with a ferritic matrix by ODS Eurofer steels with a tempered ferriticmartensitic matrix 9 and by austenitic Ni-ODS PM 1000 or Ni-ODS PM 3030.…”
Section: Introductionmentioning
confidence: 99%
“…Tests in group A were carried out to investigate the thermomechanical behaviour of different materials (1)(2)(3)(4)(5)(6)(7)(8) at different temperatures, looking at a single tensile and compression loading with a constant strain rate of 1 s -1 (Figure 7). In order to give a clearer comparison of the results, only the results at room temperature (RT), (800, 1000 and 1200)°C are presented.…”
Section: Testing Programmementioning
confidence: 99%
“…A notable improvement in the field was made by J. S. Benjamin at the International Nickel Company (INCO) laboratory: he proposed a new process based on high-energy-milling powder metallurgy -later called mechanical alloying. 2 This process was introduced to obtain a fine and homogeneous oxide dispersion within a nickel matrix. Its aim was to produce high-temperatureresistant materials for gas-turbine applications.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the nanostructure of the cryomilled materials are retained after HVOF spray because the feedstock powder is only partially molten during the spray process [13,25,37]. Subsequently, isothermal oxidation tests were carried out on these TBC samples in a Thermolyne type 48000 furnace at 1000°C in air for various lengths of time (1,2,4,8,10,50 and 100 h) to promote TGO growth. 1000°C was intentionally selected because it is within the practical operating temperature range for typical TBCs [2,3,8], as well as in-proximity-to or equal-to the temperatures considered for oxidation behavior studies that have been previously reported in the literature [13,32,33,38,39].…”
Section: Materials Processingmentioning
confidence: 99%
“…2 and 3), which remains thermally stable even after severe thermal exposure (100 h in argon at 1100°C) [21]. It has been previously reported that the presence of oxide dispersions can lead to better oxidation resistance in oxide dispersion strengthened (ODS) high temperature alloys than dispersion free alloys of the same base composition [49,50]. The oxidation mechanism controlling TGO formation in the TBCs has been previously studied, with consistent evidence that the growth of the alumina scale in the TGO usually follows parabolic growth kinetics [14,44,51].…”
Section: Growth Rate Of the Tgo Layermentioning
confidence: 99%